KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DITINJAU SELF EFFICACY : SYSTEMATIC LITERATURE REVIEW (SLR) - Aulia Adytia Putri; Dadang Juandi (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2022)
Mathematics education is very important for survival, therefore students are expected to have good mathematical abilities and attitudes, one of which is problem solving ability and self-efficacy. Solving ability problem Mathematics is one of the abilities that students must have in the 21st century. This study will examine the literature by using a systematic literature review related to how ability solving problem mathematical student self-efficacy reviewed. The literature criteria used in this research are in the form of journal articles indexed by Sinta, or Google Scholar with a maximum publication year of the last 5 years (201 8 -202 2 ). The purpose of this study is to identify, review, and draw conclusions from the literature relevant to how ability solving problem mathematical student reviewed self-efficacy in mathematics subjects. Based on the results of data analysis from the literature that became research data, the level of ability solving problem mathematical different based on self efficacy student in mathematics. By doing this research can provide information related to how ability solving problem mathematical student reviewed self-efficacy and opportunities to conduct research related to ability solving problem mathematics and self-efficacy.